An exploration of children’s views of their creative abilities in Visual Arts Education across a variety of age groups in an Irish primary school setting. - Kelly, Cristín (My University, 2021)
The overall aim for this small-scale research project was to explore children’s views of their own creative abilities in Visual Arts Education across a variety of age groups in one Irish primary school setting. A qualitative approach to this research project was adopted and data was gathered through semi-structured group interviews with children from a variety of classes. Participants also completed a creative drawing task which provided them with an opportunity to create and also initiated the discussions surrounding their creativity. Results from the study revealed that the participants had many valuable insights to offer into their creative abilities and processes during Visual Arts Education. The children specified what inspires them, where they get ideas from and highlighted factors that both influence and limit their creative processes. The children stated their need for more time, advance notice, extra materials and peer interaction during their creative endeavours in Visual Arts Education. They also acknowledged the importance of an emphasis being placed on the process, rather than the product, during art lessons. The study suggests the need for accessing the voice of the child with regard to their own creative abilities. It further highlights the importance of exploring these views at varying stages in a child’s education as creativity is ever-fluctuating and their opinions and insights are ever-changing.
Keywords: Creativity; Creative processes; Voice of the child; Inspiration; Ideation